Chester Cricket's pigeon ride - Selden, George, 1929-; Williams, Garth (New York : Farrar Straus Giroux, 1981)
Nostalgic for his country home, Chester Cricket braves the busy city streets in search of a tree and finds a new friend in the process.
Keywords: Crickets -- Fiction; Pigeons -- Fiction; New York (N.Y.) -- Fiction